The MSRT: a critical review of english proficiency in Iran - Muhammed Parviz; Masoud Azizi (Discover Education)
Abstract This article offers a critical review of the Ministry of Science, Research, and Technology English Proficiency Test (MSRT), a high-stakes exam required for postgraduate graduation, scholarships, and certain employment positions in Iran. Despite its widespread use, the design and implementation of the MSRT raise concerns about its validity and fairness as a measure of language proficiency. Grounded in Kunnan’s [1, 2] Test Fairness Framework, this review evaluates the MSRT’s structure, content, and psychometric properties, with a focus on key dimensions such as test purpose, validity, reliability, access, and social consequences. Drawing on both empirical studies and theoretical perspectives, the article highlights critical shortcomings in areas including content relevance, transparency, authenticity, administration and alignment with educational goals. In particular, the misalignment between MSRT and the communicative and academic needs of postgraduate students undermines its usefulness and equity. The article concludes by calling for comprehensive reforms in the test’s structure and administration to ensure that it better supports fair, accurate, and contextually appropriate assessment practices. In doing so, it contributes to ongoing discussions on language testing reform in Iran’s higher education system.